The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1016/j.dsr2.2010.10.030
|View full text |Cite
|
Sign up to set email alerts
|

The characteristics of dissolved organic matter (DOM) and chromophoric dissolved organic matter (CDOM) in Antarctic sea ice

Abstract: a b s t r a c tAn investigation of coloured dissolved organic matter (CDOM) and its relationships to physical and biogeochemical parameters in Antarctic sea ice and oceanic water have indicated that ice melt may both alter the spectral characteristics of CDOM in Antarctic surface waters and serve as a likely source of fresh autochthonous CDOM and labile DOC. Samples were collected from melted bulk sea ice, sea ice brines, surface gap layer waters, and seawater during three expeditions: one during the spring to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
71
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 78 publications
(81 citation statements)
references
References 79 publications
10
71
0
Order By: Relevance
“…As DOC is further concentrated within sea ice brines, organisms living in brine are exposed to DOC concentrations that are up to 3 orders of magnitude higher than in seawater. Coloured Dissolved Organic Matter (CDOM) constitutes a significant fraction of the sea ice DOM pool and can significantly contribute to the attenuation of sunlight (particularly in the UV wavelength ranges) and serve as substrate for photochemical reactions that can remineralize the CDOM breaking it down into more labile compunds [Belzile et al 2000;Norman et al, 2011].…”
Section: Dommentioning
confidence: 99%
“…As DOC is further concentrated within sea ice brines, organisms living in brine are exposed to DOC concentrations that are up to 3 orders of magnitude higher than in seawater. Coloured Dissolved Organic Matter (CDOM) constitutes a significant fraction of the sea ice DOM pool and can significantly contribute to the attenuation of sunlight (particularly in the UV wavelength ranges) and serve as substrate for photochemical reactions that can remineralize the CDOM breaking it down into more labile compunds [Belzile et al 2000;Norman et al, 2011].…”
Section: Dommentioning
confidence: 99%
“…Studies in the strongly fluvially impacted subarctic Gulf of Finland have demonstrated the importance of CDOM as a solar UV absorber within the sea ice (Ehn et al, 2004;Uusikivi et al, 2010), the influence of riverine input on the source composition of sea ice CDOM (Granskog et al, 2006), and the distinct optical properties of CDOM in sea ice as compared to that in under-ice seawater (Ehn et al, 2004;Granskog et al, 2005). More recently, surveys have been made on the distribution, photoreactivity (Norman et al, 2011), and fluorescent characteristics (Stedmon et al, 2011b) of DOM and CDOM in Antarctic sea ice in the Weddell Sea and the South Indian Ocean off Wiles Land. The CDOM in Antarctic sea ice contains mycosporine-like amino acids (MAAs) (Norman et al, 2011) and amino-acid-like fluorescent materials that are unique to sea ice brine (Stedmon et al, 2011b).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, surveys have been made on the distribution, photoreactivity (Norman et al, 2011), and fluorescent characteristics (Stedmon et al, 2011b) of DOM and CDOM in Antarctic sea ice in the Weddell Sea and the South Indian Ocean off Wiles Land. The CDOM in Antarctic sea ice contains mycosporine-like amino acids (MAAs) (Norman et al, 2011) and amino-acid-like fluorescent materials that are unique to sea ice brine (Stedmon et al, 2011b).…”
Section: Introductionmentioning
confidence: 99%
“…Microbial EPS exist in a dynamic equilibrium from dissolved polysaccharides (dEPS <0.2 μm) to complex particulate EPS that can form gels on the millimeter to centimeter scale (8). Here we focus on the biologically relevant dissolved carbohydrates (dCHO) that constitute a substantial fraction of the DOC in sea ice (9)(10)(11)(12)(13) (Fig. 1).…”
mentioning
confidence: 99%
“…1). dCHO are concentrated from sea ice DOC by dialysis (>8 kDa), with subsequent treatment allowing the definition of four subcomponents of the total dCHO pool: (i) dissolved uronic acids (dUA), produced by ice diatoms and ice bacteria (14)(15)(16), that confer strong cross-linkages between polymer chains (8), forming low solubility EPS complexes within brine channels (8,14,17); (ii) dEPS, produced by sea ice algae (9,12,18,19) and isolated from dCHO by 70% (vol/vol) alcohol precipitation; (iii) a low solubility fraction of dEPS obtained by 30% (vol/vol) alcohol precipitation, containing complex EPS molecules (dEPS complex ), often produced by algae with reduced biological activity or when under physiological stress (9,13,19); and (iv) a fraction of highly soluble carbohydrates that are not considered EPS (dCHO non-EPS ), do not precipitate in alcohol, and are produced by many actively growing ice algae (9,14).…”
mentioning
confidence: 99%